Da internet à sala de aula: um estudo exploratório de laboratórios brasileiros de experimentação remotamente controlados para aprendizagem de Física - Nogueira, Juliana Mendes (Universidade Federal de São Carlos, 2023)
Observing that many educators have sought to use diverse teaching methodologies as a motivating tool in Physics classes, it becomes significant to study their potential, as well as to explore possible associations of different strategies, analyzing their complexities and applicability as a didactic resource. In this sense, this research sought, based on the analysis of remote Brazilian laboratories, to evaluate the limits and possibilities of associating digital information and communication technologies and experimentation. Four Brazilian laboratories that are active from their experiments were analyzed; scripts to support teachers; technological resources used for control; and availability of internet access. Due to the pandemic scenario of COVID-19, started in 2020 and reopening of schools in partial format, in 2022, Brazilian remote laboratories had their availability negatively affected, since initially twenty-five experiments were accounted for, however only thirteen experimental objects and nine teaching materials were available. It was observed that Astronomy is the area of Physics most contemplated in Brazilian remote laboratories, followed by the areas of Mechanics and Electricity. During the research, it was noticed the need to prepare the professors so that the use of the experimental apparatus can reach the objectives of a scientific learning with meanings. Nevertheless, all the analyzed equipment presented resources capable of assisting in the students' teaching-learning process.
From the internet to the classroom: an exploratory study of Brazilian remotely controlled experimentation laboratories for physics learning
Keywords: Experimentation; Experimentação; Tecnologias de Informação e Comunicação; Information and Communication Technologies; Remote Laboratory; Laboratório Remoto; Physics Teaching; Ensino de Física; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM